Metode Pembelajaran Bahasa Arab Pada Program Khusus Perkuliahan Bahasa Arab STAIN Malang - Rosyadi, A. Wahab (ULUL ALBAB Jurnal Studi Islam, 2001)
Arabic intensive course at UIIS Malang makes use of the materials taken from 'Mulakhos al Arobiyah Linnasyi 'in which offers the four-language skills in an integrated sequence. The nature of the materials requires the teacher to use the direct method. This descriptive research is intended to find out the teaching techniques employed by the teachers in their teaching learning process. 75 out of 82 teachers and 200 students were involved as the research subjects. The findings revealed that the teachers used an elective method by paying more attention on creating a more conducive language environment.